Assessment of polygenic architecture and risk prediction based on common variants across fourteen cancers - Yan Dora Zhang; Amber N. Hurson; Haoyu Zhang; Parichoy Pal Choudhury; Douglas F. Easton; Roger L. Milne; Jacques Simard; Per Hall; Kyriaki Michailidou; Joe Dennis; Marjanka K. Schmidt; Jenny Chang-Claude; et al. (Nature Communications, 2020)
In cancer many gene variants may contribute to disease etiology, but the impact of a given gene variant may have varied effect size. Here, the authors analyse summary statistics of genome-wide association studies from fourteen cancers, and show the utility of polygenic risk scores may vary depending on cancer type.